Hal yang Dapat Mendatangkan dan Menghalangi Rezeki Serta Hal yang Dapat Menambah dan Mengurangi Usia - Ica Mustika Sari; Martoyo Martoyo (STIKes Ibnu Sina Ajibarang, 2024)
This research discusses various factors that are believed to be in society's traditions and beliefs can influence a person's fortune and age. These factors include behavior, habits and beliefs that are considered to bring or hinder good fortune and increase or decrease age. This study highlights diverse religious and cultural views regarding the relationship between human actions and material blessings and longevity. Apart from that, this research also explores how these perceptions and beliefs are formed and play a role in people's daily lives. Through literature analysis and observation, this research aims to provide a comprehensive understanding of how beliefs about fortune and age can influence individual behavior patterns and life decisions.